Patchy Pulsating Aurora and its Relationship to Cold Plasma in the Magnetospheric Equatorial Plane - Rae, Kyle (Graduate Studies, 2013)
Patchy pulsating aurora occur frequently after geomagnetic disturbances. These aurora consist of patches which are typically tens to one hundred or more kilometers in spatial extent. The patches sometimes pulsate (as their name suggests) quasi-periodically. The luminosity results from upper atmospheric atoms and molecules that have been excited by electrons that precipitate onto our atmosphere from above, however it is not known what process or processes lead to the formation of the patches, in particular their shape. In this thesis I investigate the origin of the shape of the patchy pulsating aurora. To accomplish this I have created a list of 53 instances of patchy pulsating aurora which I found using a network of all-sky cameras. For each event in this list I tracked the movement of and change in longitudinal extent of these auroral patches. As well, I used an empirical magnetic field model to map the patch shapes to the magnetic equatorial plane in the magnetosphere. I then assumed that the equatorial ``image'' of the patch is a structure in the equatorial plasma. I used the same magnetic field model, and an empirical model of the magnetospheric electric field to simulate the motion of charged particles within the patch image. Finally, I mapped the evolved equatorial patch image back to the ionosphere using the magnetic field model, so that I could compare the evolution of the simulated patch footprint to the evolution of the real patch. What I found was that the motion of the real patches corresponds well to that of the ionospheric footprint of the equatorial patches provided the particles within the patch are of relatively low energy. Further, I found that in order for the evolution of the shape of the simulated patches (as mapped into the ionosphere) to match that of the real patches, the range of energies of the particles must be extremely small.